Social media at work how networking tools propel organizational performance - Jue, Arthur L. 1966-; Marr, Jackie Alcalde 1962-.; Kassotakis, Mary Ellen 1953-. (San Francisco Jossey-Bass, 2010)
"The definitive guide for using social media to build more effective organizations. Today?s networking technologies-wikis, blogs, and social networking sites-are changing how we build professional relationships and work collaboratively. In this insightful book, three organizational development experts from Oracle Corporation offer executives down-to-earth strategies for leveraging the power of social media to build more effective and agile organizations, engage employees, and sustain competitiveness. Offers practical advice for using social media (wikis, blogs, and social networking sites) to increase organizational effectiveness. Presents proven recommendations for building teams, accelerating learning, and fostering innovation by adopting social networking tools. Shows how to tap into the power of social networks to improve organizational performance. Demonstrates how social media will help organizations thrive for years to come by drawing on case studies from companies like Intel, Cisco, Nokia, and others"--Provided by publisher.
Social media at work -- The changing landscape and what it means to you -- What is social media, and how does it work? -- Where social media has an impact -- Examples from trailblazers -- Putting social media to work -- Looking to the future -- Notes -- Acknowledgments -- About the authors -- Index.
Keywords: Social media; Social networks; Organization